Disinfection technology of hospital wastes and wastewater: Suggestions for disinfection strategy during coronavirus Disease 2019 (COVID-19) pandemic in China. (July 2020) - Wang, Jiao; Shen, Jin; Ye, Dan; Yan, Xu; Zhang, Yujing; Yang, Wenjing; Li, Xinwu; Wang, Junqi; Zhang, Liubo; Pan, Lijun
Abstract: Hospitals are important sources of pollutants resulted from diagnostic, laboratory and research activities as well as medicine excretion by patients, which include active component of drugs and metabolite, chemicals, residues of pharmaceuticals, radioactive markers, iodinated contrast media, etc. The discharge of hospital wastes and wastewater, especially those without appropriate treatment would expose the public in danger of infection. In particular, under the Coronavirus Disease 2019 (COVID-19) pandemic context in China, it is of great significance to reduce the health risks to the public and environment. In this study, technologies of different types of hospital wastes and wastewater disinfection have been summarized. Liquid chlorine, sodium hypochlorite, chlorine dioxide, ozone, and ultraviolet irradiation disinfection are commonly used for hospital wastewater disinfection. While incineration, chemical disinfection, and physical disinfection are commonly used for hospital wastes disinfection. In addition, considering the characteristics of various hospital wastes, the classification and selection of corresponding disinfection technologies are discussed. On this basis, this study provides scientific suggestions for management, technology selection, and operation of hospital wastes and wastewater disinfection in China, which is of great significance for development of national disinfection strategy for hospital wastes and wastewater during COVID-19 pandemic. Graphical abstract: Image 1 Highlights: O3, UV, chlorine disinfectants are used for hospital wastewater disinfection. Incineration, chemical and physical techniques are used to disinfect hospital wastes. Providing suggestions for hospital wastes and wastewater disinfection during COVID-19. The chlorine disinfection and incineration are primarily recommended.